2006
DOI: 10.1007/s10753-006-9015-x
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytes in Complex Regional Pain Syndrome Type I

Abstract: We found a significantly increased accumulation of leukocytes in patients with CRPS I. This is the first study to show a possible role for leukocytes in the pathophysiology of acute CRPS I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Furthermore, elevated levels of IL-8 and sTNF-RI/II indicate an association between CRPS1 and an inflammatory process. A recent finding suggests that there is an ongoing inflammatory response in the form of increased leukocyte accumulation on the involved side (Tan et al, 2005). Another finding supporting the theory of an excessive inflammatory reaction is the increased extravasation of indium-labelled immunoglobulin as a sign of increased capillary permeability to macromolecules (Oyen et al, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, elevated levels of IL-8 and sTNF-RI/II indicate an association between CRPS1 and an inflammatory process. A recent finding suggests that there is an ongoing inflammatory response in the form of increased leukocyte accumulation on the involved side (Tan et al, 2005). Another finding supporting the theory of an excessive inflammatory reaction is the increased extravasation of indium-labelled immunoglobulin as a sign of increased capillary permeability to macromolecules (Oyen et al, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…This study has demonstrated an increase in the percentage of the CD14 + CD16 + monocyte subgroup in individuals afflicted with CRPS. In addition, other investigators have reported mast cell involvement [47], leucocyte accumulation in the affected extremity [48] and impaired neutrophil function [49] in patients with CRPS. Thus, further evaluation of the role the immune system plays in the pathogenesis of CRPS is warranted, and may aid in elucidating disease mechanisms as well as the development of novel therapies for its treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, an exaggerated expression of pro‐inflammatory cytokines in cerebrospinal fluid and even in venous blood has been determined . An enhanced migration of injected radiolabelled leukocytes and human polyclonal nonspecific immunoglobulins toward CRPS‐affected locations was shown in scintigraphic studies . Furthermore, increased intima‐media thickness of the radial and brachial artery was measured with ultrasound in CRPS‐1 affected limbs compared to the intima‐media thickness in arteries of pain‐free controls, which suggests ongoing inflammation …”
Section: Endothelial Dysfunctionmentioning
confidence: 98%